The Protective Effect of Basic Fibroblast Growth Factor on Diabetic Nephropathy Through Remodeling Metabolic Phenotype and Suppressing Oxidative Stress in Mice - Wei, Tingting; Shu, Qi; Ning, Jie; Wang, Shuaijie; Li, Chen; Zhao, Liangcai; Zheng, Hong; Gao, Hongchang (Frontiers in Pharmacology, 2020)
Diabetic nephropathy is a common complication in diabetes, but still lack of effective therapeutic strategies. This study aimed to investigate the therapeutic effect of basic fibroblast growth factor (bFGF) in db/db mice with diabetic nephropathy and explore its possible metabolic mechanisms using a nuclear magnetic resonance-based metabolomic approach. We found that bFGF treatment significantly alleviate urinary albumin to creatinine ratio and renal fibrosis in db/db mice, suggesting a potential renal protective effect. Metabolomics results reveal that bFGF remodeled metabolic phenotypes of the kidney and urine in db/db mice, mainly involving energy metabolism, methylamine metabolism, osmoregulation, and oxidative stress. Furthermore, the results show that bFGF-induced reductions of oxidative stress and apoptosis in db/db mice might be mediated by NOX-ROS-Nrf2 signaling. Therefore, our study suggests that the protective effect of bFGF on diabetic nephropathy could be mediated by remodeling metabolic phenotype and suppressing oxidative stress.